Cultivating Tech-Savvy Communities: Revitalizing Digital Literacy in Palembang City - Isabella, Isabella; Alfitri, Alfitri; Saptawan, Ardiyan; Nengyanti, Nengyanti; Mahadika, Alam (Journal Public Policy, 2024)
This digital literacy is motivated by the COVID-19 Pandemic, people must adapt to new cultures such as work, school, and economic activities through online media. Advances in digital-based information technology cannot be stopped anymore and have become part of today's society's need., For this reason, it is necessary to increase public knowledge in the field of digital literacy. This study aims to determine the implementation of digital literacy programs in the community in Palembang City, among and students. This study uses a qualitative method, using the four pillars of digital literacy, digital skills, digital culture, digital ethics, and digital safety. The theory used in this study is the implementation theory of Grindle, in which determined by the content of the policy and the context of its implementation. The basic idea of this theory is that after the policy is transformed, its implementation takes place. Data analysis in this study used interactive model analysis of qualitative data from Miles and Saldana consisting of Data Condensation, Data Display, and Conclusion drawing or verifications. Based on this research, the four pillars of digital literacy are very important indicators in digital literacy programs. Digital skills are the most basic pillars of interest for the public to learn as basic knowledge of digital literacy. Then followed by digital ethics as further knowledge that needs to be studied so that people know ethics when using digital media. Based on this research, it can be concluded that the implementation of digital literacy will be successful if it is also supported by regulations, rules, and policies for equal distribution of internet networks in all regions of Indonesia, including in the city of Palembang. The government and relevant stakeholders should continuously improve the facilities and infrastructure related to digital literacy, such as expanding stable internet networks and boosting the economy through the development of various online businesses. The shared programs between the government and other communities in educating the masses need to be implied regulary, so that the people, especially in Palembang have an increase of digital literacy as a whole.